Analisis Konsep Fitrah dan Kecerdasan Majemuk dalam Perspektif Psikologi Pendidikan Islam - Khotma Guntur; Shindid Gunagraha (Halaqatuna, 2026)
This research aims to examine conceptually and empirically how the approach to Islamic education psychology can maximize the development of students' potential holistically. This research is motivated by the challenges of Islamic education in dealing with the diversity of potential and character of students through the humanism approach, because every potential is a fitrah that has been determined by Allah SWT. In addition, there is a phenomenon in formal educational institutions that shows that there is still an emphasis on uniformity and ignores the uniqueness of students so that it is possible to limit potential development. The research method uses literature research to explore the concept of Islamic educational psychology from classical and contemporary sources. The results of the study show that the approach to Islamic education psychology based on the concepts of fitrah, tarbiyah, and the recognition of individual potential is able to create a more adaptive, empathetic, and transformative learning. That with this approach, teachers are able to carry out learning not only for the purpose of knowledge intelligence but also to foster spiritual awareness which will have an impact on increasing learning motivation and learning achievement of students. The conclusion of this study emphasizes that every child is unique and educated, Islamic teachings provide space to develop this uniqueness in a balanced manner between intellectual, emotional, and spiritual aspects. It is possible to integrate the principles of Islamic educational psychology into pedagogical practice, it is hoped that education can be more inclusive and meaningful for every student.